Study on the year-round fluctuation of total lipid content and lipid classes composition in soft coral \(Sinularia flexibilis\) from Nha Trang, Khanh Hoa coastal area - Dao Thi, Kim Dung; Pham Minh, Quan; Pham Quoc, Long; Nguyen Thi, Nga; Dinh Thi, Tu; T. V., Sikorskaya; E. V., Ermolenko; Dang Thi, Phuong Ly; Nguyen Anh, Hung (Vietnam Journal of Marine Science and Technology, 2022)
Samples of soft coral Sinularia flexibilis were collected for one year, from January to December, in the Nha Trang coastal area, Khanh Hoa province, to assess the month-by-month fluctuation of total lipid content and lipid classes composition in this species. Full lipid content reached the highest value from March to May, lower in the period of June-September, and bottomed in October and November. There was a significant decrease in this content between May and June, September and October; the content increased from February to March but was not stable from October to February. The lipid classes composition of Sinularia flexibilis includes polar lipids (PL), sterols (ST), triacylglycerol (TAG), monoalkyldiacyl-glycerol (MADAG), wax (W), and free fatty acids (FFA). The concentration of PL in summer (April-August) was lower than that in winter (September-February); this content increased significantly during November-December; meanwhile, it was observed to decrease in April-May, December-January. The content of ST increased from October to March and declined from April to September. The remaining classes, including W, MADAG, and TAG, tend to grow in the summer and decline in the other months. The fluctuation of lipid class composition throughout the year is closely related to zooxanthellae microalgae in corals at different times of the year and is directly influenced by environmental conditions, especially seawater temperature. Besides, this coral’s maturation and reproduction effect with the increase or release of reproductive materials was also observed.